La Storia illustrata dell’educazione di Mario Alighiero Manacorda tra divulgazione e ricerca scientifica: limiti e novità - Silvestri, Luca (Studi sulla Formazione/Open Journal of Education, 2024)
This paper aims to highlight some of the unique characteristics of Mario Alighiero Manacorda’s Storia illustrata dell’educazione, demonstrating its originality in the field of historical-educational studies related to iconography. Firstly, the work’s dual purpose, which is both popular and scientific, will be examined in relation to Giunti’s publishing policy. Then, the limits and potential of the work will be identified in order to show that, as is often the case with avant-garde works, it is not free of contradictions. These contradictions can still be read today in a way that is fruitfully for future historical-educational research on iconography.